Queer Language in Italian Audiovisual Translation - Cuscito, Miriam (My University, 2024)
This study examines the audiovisual translation of queer language, elements, and themes through a contrastive analysis of the Italian reception of the movie “If These Walls Could Talk II”, created by HBO in 2000 and the British series “Sex Education”, first released in January 2019 on Netflix. Several scholars have investigated the role of queer topics in translation, highlighting the tendency to censor potentially problematic or ideologically marked concepts in the target culture. The aim is to call attention to the level of censorship, the strategies related to the period of production and distribution, genre, and reception throughout a diachronic analysis which accounts for audiovisual products circulating with almost twenty years of distance. The research’s findings highlight a strict relationship among prevailing ideology, temporality and censorship in the Italian rendering of queer language and offer some new perspectives to manage the language of queer related issues.
Keywords: Censorship; Film; Language; LGBTIQ; Queer; ddc:450